2013
DOI: 10.1021/mz400171e
|View full text |Cite
|
Sign up to set email alerts
|

Buckminsterfullerene: A Strong, Covalently Bonded, Reinforcing Filler and Reversible Cross-Linker in the Form of Clusters in a Polymer

Abstract: A Buckminsterfullerene/polyisoprene (C 60 /PI) composite was synthesized at high-temperature, high-pressure (HP&HT) conditions. The composite has significantly improved tensile strength and Young's modulus, by up to 49% and 88% per wt % C 60 , respectively, which is much higher than for corresponding composites with carbon nanotube (CNT) fillers. The reinforcing action of C 60 fillers is different from that of CNTs as C 60 becomes covalently bonded to PI chains, and C 60 clusters in PI form C 60 −C 60 covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This The FTIR spectra (Fig. 4) Therefore, during the MAPLE deposition process, the behavior of added C 60 and its incorporation in polymer is difficult to predict: it can be dispersed creating single molecule bridges between the polymer chains or can form clusters [33]. The UV laser radiation used in our MAPLE configuration can break the double bonds on two adjacent C 60 molecules creating C 60 dimmer, the C 60 molecules can react with neighboring C 60 molecules generating oligomeric or polymeric forms.…”
Section: Page 8 Of 45mentioning
confidence: 99%
“…This The FTIR spectra (Fig. 4) Therefore, during the MAPLE deposition process, the behavior of added C 60 and its incorporation in polymer is difficult to predict: it can be dispersed creating single molecule bridges between the polymer chains or can form clusters [33]. The UV laser radiation used in our MAPLE configuration can break the double bonds on two adjacent C 60 molecules creating C 60 dimmer, the C 60 molecules can react with neighboring C 60 molecules generating oligomeric or polymeric forms.…”
Section: Page 8 Of 45mentioning
confidence: 99%
“…In addition, in irradiated CNTs-filled polyisoprene composites by powerful radiation, H 2 atoms of the chain, chiefly groups of methylene proportional to double bonds are ejected and radical sites are formed and combined into C-C cross-links. However, the radiation cross-linking efficiency of polyisoprene is insignificant, because of the loose packing of polyisoprene molecules with the cis structure and the groups of methyl (Yu et al 2013a, b).…”
Section: Cnts: In Polyisoprene Polymeric Compositesmentioning
confidence: 99%
“…The results of the cross-linking and inclusion of CNTs into polyisoprene studied by in situ thermal conductivity and tensile test revealed that Polyisoprene reinforced MWCNTs composite showed an increment in stiffness with growing MWCNTs content, retained stiffness to large strains, but with the increase in MWCNTs content the failure strains decreased (Yu et al 2013a, b).…”
Section: Cnts: In Polyisoprene Polymeric Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7,10,[11][12][13] Meanwhile, superstrong thermoplastic polymers are usually difficult to dissolve in proper solvents and to process. 3,5,14,15 A conventional and widely employed strategy for reinforcement of thermoplastic polymers is homogeneously dispersing stiff nanofillers, such as silica, 9,16 clays, 10,17,18 carbon nanotubes, [19][20][21] graphene oxides, 20,[22][23][24] cellulose nanocrystals, 25,26 metal nanoparticles, 27,28 and other nanofillers 3,[29][30][31] within them. Uniform nanofiller dispersion and strong interfacial interactions between nanofillers and polymer matrices are the most crucial factors that enhance the mechanical strength of the resulting polymer composites.…”
Section: Introductionmentioning
confidence: 99%